Addressing the barriers to optimal management of febrile neutropenia in children with cancer. (April 2020) - Anderson, Katrina; Bradford, Natalie; Edwards, Rachel; Nicholson, Jessica; Lockwood, Liane; Clark, Julia
Abstract: Purpose: Fever and associated neutropenia presentations are frequent occurrences for children with cancer. Prompt treatment is required to prevent adverse outcomes; however, delays are common. In Australia's vast landscape, presentations occur in both tertiary metropolitan sites and smaller regional sites. Management and experiences differ between sites. Our primary aim was to identify the barriers to optimal management of febrile neutropenia in children with cancer from patient/parent and clinician perspectives. Methods: A mixed methods approach was used where quantitative data was supplemented by qualitative data. Data were prospectively collected from parents (n=81) and clinicians (n=42) about all children who presented with fever across multiple diverse hospital locations. A subset of parents (n=9) and clinicians (n=19) completed semi-structured interviews. Results: Delays in assessment and treatment were reported by 31% of parents and up to 36% of clinicians. Four distinct time points where delays occurred were identified: 1) pre-presentation; 2) initial assessment; 3) blood collection and establishing intravenous access, and 4) preparation and administration of antibiotics. Although reasons for delay were diverse, they were primarily related to clinician's knowledge and awareness of fever management, and intravenous access device factors. Interventions were formulated to target these barriers and streamline processes. Conclusion: We identified multifactorial reasons for delays at different time points in care. Regional centres and families have unique needs which require considerations and tailored interventions. Ongoing education, monitoring compliance with initiation of practice changes and identifying and overcoming barriers as they arise are strategies for improving management of the febrile child with cancer. Highlights: Problem: Fever and neutropenia are potentially life-threatening events for children with cancer. What is already known: Prompt management is required; yet delays often occur. Most studies have focussed on management in metropolitan centres, few have evaluated smaller regional centres where many patients present. What this paper adds: Four distinct time points were identified when delays occur . We developed interventions relevant across cancer centres for each time point to address identified barrier to optimal care.